Early Development Of Catfish Larvae Sangkuriang (Clarias gariepinus) From Feed With The Addition Of Curcumin - Febry Ramadhani; Annisyah Putri Amalia Sipahutar; Sari Sekar Wangi (Berkala Perikanan Terubuk, 2023)
This study aims to identify the quality of spawning eggs and body length in the early development of catfish larvae from broodstock fed with the addition of curcumin. This research was conducted on October 22 2022 for 2 weeks on Jl. Great Aluminum No. 37, Tj. Mulia Hilir, Kec. Medan Deli, Medan City, North Sumatra 20241. The method used in this research is an experimental method. The sample used is sangkuriang catfish seeds (Clarias gariepinus) obtained from catfish breeding/cultivation. There are 2 pairs in total. Each pair consists of male and female catfish which are placed in the same pond but have been partitioned off. One pair of sangkuriang catfish will be given feed in the form of pellets with the addition of curcumin while the other pair will only be given pellets. The treatment in giving curcumin is 50% of the feed weight once a day the average body length of larvae has a body length and body weight that is higher than curcumin was not given so that the 0% curcumin treatment had the lowest body length. The increase in the diameter of the spawning larvae in the supplemented treatment group curcumin can be caused due to the bioactivity of curcumin as a hepatoprotector, and antioxidants. Curcumin supplementation is 50% of the total feed given to the parent showed more optimal results than the treatment other.